2021
DOI: 10.3390/molecules26195795
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, Development, and Patent Trends on Molnupiravir: A Prospective Oral Treatment for COVID-19

Abstract: The COVID-19 pandemic needs no introduction at present. Only a few treatments are available for this disease, including remdesivir and favipiravir. Accordingly, the pharmaceutical industry is striving to develop new treatments for COVID-19. Molnupiravir, an orally active RdRp inhibitor, is in a phase 3 clinical trial against COVID-19. The objective of this review article is to enlighten the researchers working on COVID-19 about the discovery, recent developments, and patents related to molnupiravir. Molnupirav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
157
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(172 citation statements)
references
References 41 publications
0
157
0
1
Order By: Relevance
“…However, studies have shown that even vaccinated people are infected with novel coronavirus variants. Millions of immunocompromised patients may not be fully protected after vaccination, and existing vaccines may not be effective against new novel coronavirus variants [ 4 , 5 ]. Although an antiviral drug Remdesivir has been developed that has shown good effects in antiviral therapy [ 6 ], some clinical trials have not fully demonstrated its beneficial effects on SARS-COV-2; moreover, the drug is expensive and must be administered intravenously in a hospital setting [ 6–8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that even vaccinated people are infected with novel coronavirus variants. Millions of immunocompromised patients may not be fully protected after vaccination, and existing vaccines may not be effective against new novel coronavirus variants [ 4 , 5 ]. Although an antiviral drug Remdesivir has been developed that has shown good effects in antiviral therapy [ 6 ], some clinical trials have not fully demonstrated its beneficial effects on SARS-COV-2; moreover, the drug is expensive and must be administered intravenously in a hospital setting [ 6–8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especifically, molnupiravir (aka EIDD‐2801 and MK‐4482) induced RNA mutagenesis by the viral RNA‐dependent RdRp. Molnupiravir showed an exciting experimental results in phase 2 clinical trials, and was one of the most promising small molecule anti‐coronavirus drugs at present (Imran et al, 2021 ; Kabinger & Stiller, 2021 ; Malone & Campbell, 2021 ). In October 2021, Merck Co. submitted an Emergency Use Authorization (EUA) application to the US Food and Drug Administration (FDA) for molnupiravir based on the promising results from the Phase 3 MOVeOUT clinical trial (Press releas, Merck Company website, 2021).…”
Section: Types Of Agents In Clinical Trailsmentioning
confidence: 99%
“…Different types of patents are possible for a pharmaceutical compound including patents claiming compound, salt, isomer, polymorph, process, intermediate used in the process, drug impurity, method of treatment, different dosage forms, particle size, and drug combinations [ 70 , 71 , 72 , 73 ]. The types of patents/patent applications related to mobocertinib are mentioned in Figure 7 .…”
Section: Expert Opinionmentioning
confidence: 99%
“…In early 2017, Takeda acquired Ariad Pharmaceuticals and became the owner of the patents filed by Ariad Pharmaceuticals. These two patents are eligible for patent term extension up to five years [ 70 , 71 , 72 , 73 ]. If this happens, these patents will expire by 2040.…”
Section: Expert Opinionmentioning
confidence: 99%